2017
DOI: 10.1186/s12904-016-0181-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trials in palliative care: a systematic review of their methodological characteristics and of the quality of their reporting

Abstract: BackgroundOver the past decades there has been a significant increase in the number of published clinical trials in palliative care. However, empirical evidence suggests that there are methodological problems in the design and conduct of studies, which raises questions about the validity and generalisability of the results and of the strength of the available evidence. We sought to evaluate the methodological characteristics and assess the quality of reporting of clinical trials in palliative care.MethodsWe pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 52 publications
0
54
0
1
Order By: Relevance
“…63,65 Conversely, palliative care research has been growing, and many of the most recent clinically influential studies in the field have been centered around oncological diseases. 66 Although well developed in survivorship care, pediatric palliative care still is very much a growing field, and opportunities to further emphasize research in this area remain. [67][68][69] International studies have shown various benefits of the earlier integration of palliative care in terms of QOL, health care use, levels of patient and caregiver distress, and even survival.…”
Section: Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…63,65 Conversely, palliative care research has been growing, and many of the most recent clinically influential studies in the field have been centered around oncological diseases. 66 Although well developed in survivorship care, pediatric palliative care still is very much a growing field, and opportunities to further emphasize research in this area remain. [67][68][69] International studies have shown various benefits of the earlier integration of palliative care in terms of QOL, health care use, levels of patient and caregiver distress, and even survival.…”
Section: Researchmentioning
confidence: 99%
“…Conversely, palliative care research has been growing, and many of the most recent clinically influential studies in the field have been centered around oncological diseases . Although well developed in survivorship care, pediatric palliative care still is very much a growing field, and opportunities to further emphasize research in this area remain .…”
Section: Introductionmentioning
confidence: 99%
“…Recruitment to clinical trials in people with advanced disease or in palliative care can be particularly challenging. For example, a recent systematic review found the target sample size was only achieved in 36.8% of trials assessing a therapeutic intervention [2]. Eligibility can be a major limiting factor affecting recruitment in advanced disease.…”
Section: Introductionmentioning
confidence: 99%
“…As more people approach the end of their lives with chronic and complex conditions, the need for robust research and evidence has never been greater. However, clinical trials in palliative care remain sparse, often limited by poor funding and methodological weaknesses [2,27,28]. It is therefore important to understand what affects retention so that we can minimise attrition and ensure high-quality clinical trials of palliative care interventions in the future.…”
Section: Introductionmentioning
confidence: 99%
“…However, strategies to improve recruitment into trials have had variable success (3). As more people approach the end of their lives with chronic and complex conditions, the need for robust research and evidence has never been greater, however clinical trials in palliative care remain sparse often limited by poor funding and methodological weaknesses (2,21,22). It is therefore important to understand what affects retention so that we can minimise attrition and ensure high quality clinical trials of palliative care interventions in the future.…”
Section: Introductionmentioning
confidence: 99%